2009
DOI: 10.1111/j.1440-1843.2008.01466.x
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of a bronchial drainage technique (ELTGOL) in COPD exacerbations

Abstract: Chest physiotherapy using the ELTGOL technique has a limited role in patients with mild exacerbation of moderate to severe COPD with a tendency towards fewer exacerbations and hospitalizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 15 publications
3
31
1
2
Order By: Relevance
“…By contrast, all the studies on chest therapy showed significant results in dyspnea perception 22,32,38 when measured. Only the study by Kodric and colleagues 38 found that the ELTGOL technique, used twice a day, resulted in significant improvements in the frequency of future exacerbations; no other study found these differences at follow-up. The differences may be due to the compliance developed by subjects when they learned the technique at the hospital.…”
Section: Chest Physical Therapymentioning
confidence: 78%
See 2 more Smart Citations
“…By contrast, all the studies on chest therapy showed significant results in dyspnea perception 22,32,38 when measured. Only the study by Kodric and colleagues 38 found that the ELTGOL technique, used twice a day, resulted in significant improvements in the frequency of future exacerbations; no other study found these differences at follow-up. The differences may be due to the compliance developed by subjects when they learned the technique at the hospital.…”
Section: Chest Physical Therapymentioning
confidence: 78%
“…Physiotherapy modalities explored in the trials included exercise sessions with aerobic or resistance exercise, 26,30,36 expiration with glottis open in lateral posture (ELTGOL), 38 PEP, 27 intrapulmonary percussive ventilation, 32 NMES, 33,34 manual chest therapy and active cycle of breathing techniques, 29,31,35 a controlled breathing program, 28 and either standard physical therapy 37 (not specified) or combined training, including breathing techniques and exercise. [23][24][25] Table 3 shows the full details on treatment and interventions for each study.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…7 However, studies analyzing ELTGOL have been performed only during exacerbations. 8,9 The purposes of this study were to evaluate the effects of ELTGOL on mucus clearance, especially in peripheral lung areas, in stable patients with chronic bronchitis, and to compare the efficacy of this technique in both lungs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the potential benefits of this technique are the improvement of peripheral airway clearance 9 and dyspnea, and the reduction in disease exacerbations 10 . The ELTGOL consists of performing slow expirations with the glottis opened, from the functional residual capacity (FRC) to the residual volume (RV), with the individual in the lateral decubitus position with the affected lung in the dependent position 11 .…”
Section: Introductionmentioning
confidence: 99%